Inhibitory effects of daun sendok (Plantago major L.) on mast cell-mediated anaphylactic reaction - Agung Endro Nugroho; Erna Prawita Setyowati; Zullies Ikawati (Indonesian Journal of Pharmacy, 2004)
Hypersensitisation reaction, which is known as an allergy, is suffered by a lot of people in the modern society. An increase of allergen uptake and the decrease of immune system are considered to be the major factors, which influence the disease. Development of medicinal plants for the allergic reaction is continuing with the extract of Plantago major as an example. This extract could inhibit histamine release from cell culture of Rat Basophilic Leukaemia (RBL-2H3) induced by DNP-BSA in vitro. This study determined the effect of Plantago major L. on systemic anaphylactic reaction induced by compound 48/80 in vivo.The research was conducted using Balb/c mice (2-3 months, 20-30 gram) which were divided into 2 main groups i.e. (1) those which were given with etanol extract on systemic anaphylactic reaction, and (2) those which were given with n-hexane extract on systemic anaphylactic reaction. Each group was divided into five sub-groups based on various dosages of Plantago major extract i.e. 0.1, 1.0, 10.0, 100.0, 1000.0 mg/kg BW. Compound 48/80, a histamine release inductor, was administered at dose of 8 mg/kg BW, an hour after Plantago major administration, and the total of death mice were observed for an hour. Pharmacological parameter, ED50 value, was determined using probit analysis.The result showed that both etanol and n-hexane extracts of Plantago major L could inhibit systemic anaphylactic reaction induced by compound 48/80 with ED50 values of 1.66 and 55.01 mg/kg BW, respectively. It can be concluded that the potency of etanol extract of Plantago major L is higher than its n-hexane extract.Key words: Plantago major L., anaphylactic, histamine and mast cells